Ethnobotanical information on Sapium insigne (Royle) Benth.: A conserved plant of Shivalik hills, India - Rawat, Dhiraj S.; Kharwal, Anjna D. (Bangladesh Journal of Plant Taxonomy, 2010)
Not available. Keywords: Ethnobotanical information; Latex; Shivalik hills. DOI: 10.3329/bjpt.v17i1.5396 <span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman"; mso-bidi-font-size: 12.0pt;">Bangladesh<span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman"; mso-bidi-font-size: 12.0pt;"> J. Plant Taxon. 17(1): 97-99, 2010 (June)